Staffing as a lever of strategic change - theinfluence of managerial experience, behaviour and values - Rieple, Alison (Cranfield University, 1995)
This paper is based on an interpretative study of an entire management team within a single company. It examines the factors such as the values, experience, and behaviours of new managers within the company which influenced their assimilation, and thus affected the effectiveness of the organisation at a particular moment in time. In this case the firm had a new chief executive who was attempting to re-focus the company’s strategic position, and new staff were intended to be a major lever with which to effect change. However, it was widely perceived that some of the new managers were less successful in this than they might have been. This paper therefore reports on the factors which appeared to contribute to their relative failure.